Socio-economic consequences of the Chernobyl nuclear power plant disasterfor the Republic of Belarus - Tsybulka, Mikalai M.; Shmeleva, Ekaterina V. (Journal of the Belarusian State University. Ecology, 2026)
The article presents a methodology and a comprehensive assessment of the socio-economic damage caused to the Republic of Belarus as a result of the disaster at the Chernobyl nuclear power plant. The damage calculation method included the use of a system of indicators based on a detailed accounting of a significant number of primary factors that predetermine the magnitude of economic and social losses from radioactive contamination of the territory. Where necessary, the primary parameters of the studied factors, obtained in kind, were converted into cost indicators using the appropriate quantitative dependencies. A comprehensive assessment conducted using the presented methodology showed that the total damage caused to the Republic of Belarus as a result of the disaster at the Chernobyl nuclear power plant, calculated for the period from 1986 to 2015, amounted to USD 235 billion. In the structure of the total damage, the largest share (81.6 %) was accounted for by additional costs of eliminating the consequences of the accident, which amounted to USD 191.7 billion. Direct and indirect losses amounted to approximately USD 30.0 billion, or 12.6 %, while lost profits amounted to USD 13.7 billion, or approximately 6 %. Agriculture suffered the most in the real economy. As a result of the accident, 1,866 thousand hectares of agricultural land were exposed to radioactive contamination. 264,500 hectares of land were withdrawn from circulation. Among the total damage caused by the Chernobyl disaster, a special place is occupied by the assessment of damage associated with changes in human health. Calculations have shown that damage to human health from the emergency radiation dose is equal to USD 288.8 million, from the expected radiation dose during 1986–1990 – USD 64.4 million, and for the entire period under review (1986-2015) – USD 177.5 million.